Using Cultural Capital in the ESL Classroom: One Teacher’s Journey - Pollock, Dovis (Issues in Language Instruction, 2018)
Bourdieu’s concept of cultural capital can help ESL instructors develop professionally and can lead to other related concepts that can address behavioral issues in the classroom and facilitate instruction. To illustrate my professional journey, I begin by focusing on a simple definition of cultural capital and consider how it relates to other areas such as soft skills and metacognitive skills. The educational experiences with respect to cultural capital and other skills that many of our international students have can vastly differ from what is found in American classrooms. This is especially true of students who have been taught in a culture where they memorize facts, do not ask questions or argue their point of view, and have not been involved in any creative process related to learning. Therefore, it is important to explicitly teach these skills. I conclude by sharing some examples of how I addressed and taught cultural capital in the classroom and give ideas of how to create one’s own mini-lessons.